2021
DOI: 10.1111/cpr.13092
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell infiltration, contribution and regulation in the central nervous system post‐traumatic injury

Abstract: T cells participate in the repair process and immune response in the CNS post‐traumatic injury and play both a beneficial and harmful role. Together with nerve cells and other immune cells, they form a microenvironment in the CNS post‐traumatic injury. The repair of traumatic CNS injury is a long‐term process. T cells contribute to the repair of the injury site to influence the recovery. Recently, with the advance of new techniques, such as mass spectrometry‐based flow cytometry, modern live‐cell imaging, etc,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…T lymphocytes play important roles in the pathogenesis of neuroinflammation following CNS injury. 91 As a key modulator of the adaptive immune response, CD4+ T cells mainly differentiate into four subtypes—Th1, Th2, Th17, and Treg cells—that are essential for affecting the outcome of inflammatory response by restricting or activating other immune cell responses. 92 , 93 Each CD4+ T cell subtype has a specific transcriptional program and cytokine expression pattern that can aggravate or mitigate the degree of secondary injury.…”
Section: Contribution Of Distinct Immune Cells To Sci Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…T lymphocytes play important roles in the pathogenesis of neuroinflammation following CNS injury. 91 As a key modulator of the adaptive immune response, CD4+ T cells mainly differentiate into four subtypes—Th1, Th2, Th17, and Treg cells—that are essential for affecting the outcome of inflammatory response by restricting or activating other immune cell responses. 92 , 93 Each CD4+ T cell subtype has a specific transcriptional program and cytokine expression pattern that can aggravate or mitigate the degree of secondary injury.…”
Section: Contribution Of Distinct Immune Cells To Sci Inflammationmentioning
confidence: 99%
“…Apart from Th1 and Th2 cells involved in the neuroinflammation, study has shown that both Th17 cells and Treg are essential to regulate the immune response post-SCI. 91 Th17 cells are defined by the characteristic production of IL-17A, IL-17F, IL-21, and IL-22 along with the expression of the master transcription factor RORγt. 102 Th17 cells are pro-inflammatory and essential to protect against pathogens by recruitment of neutrophil granulocytes.…”
Section: Contribution Of Distinct Immune Cells To Sci Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Th1 cells permeabilize the BBB to secrete chemokines essential for leukocyte trafficking into the cerebral spinal fluid ( 139 ). Th2 cells require IL- 4 and the transcription factor GATA3 and produce neuroprotective cytokines, such as IL- 4, IL- 5, IL- 10, and IL- 13 and induce macrophages with rather anti-inflammatory phenotypes ( 140 ). After TBI, Th polarization is mediated by the TLR4 receptor on myeloid cells.…”
Section: Systemic Immune Responsementioning
confidence: 99%
“…T reg are CD4 + T cells that express Foxp3 and CD25 ( 153 ) and are capable of differentiating into natural Treg cells (nTreg) and inducible Treg cells (iTreg); nTreg cells are the primary cells to infiltrate the CNS parenchyma after trauma ( 140 ). After reaching the site of injury, Treg secrete anti-inflammatory cytokines such as IL-10 and TGF-β, but also inhibit various immune cells such as circulating monocyte-derived macrophages or dendritic cells and limit neuroinflammation and brain damages.…”
Section: Systemic Immune Responsementioning
confidence: 99%